Decolonizing Food Justice: Naming, Resisting, and Researching Colonizing Forces in the Movement. Issue 1 (17th June 2015) - Bradley, Katharine; Herrera, Hank
Abstract: Over the past 15 years social movements for community food security, food sovereignty, and food justice have organized to address the failures of the multinational, industrial food system to fairly and equitably distribute healthy, affordable, culturally appropriate real food. At the same time, these social movements, and research about them, re‐inscribe white, patriarchal systems of power and privilege. We argue that in order to correct this pattern we must relocate our social movement goals and practices within a decolonizing and feminist leadership framework. This framework challenges movement leadership and scholarship by white people who uncritically assume a natural order of leadership based on academic achievement. We analyze critical points in our collaboration over the last four years using these frameworks. Doing so highlights the challenges and possibilities for a more inclusive food justice movement and more just scholarship.